2021
DOI: 10.31234/osf.io/48xjr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood temperament and adulthood personality differentially predict life outcomes

Abstract: Debate has long since surrounded whether temperament and personality traits are completely distinct sets of individual differences or are rather two sides of the same coin. One way to test this is to examine the joint and unique predictive validity of each set of traits in the same individuals across time. Using a sample of N = 7,081 individuals with ages ranging from infancy to 37 years old, we ran a series of Bayesian generalized linear models with measures of childhood temperament and adult-based personalit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…According to the differential pathways hypothesis, the pathways that explain why personality traits impact future outcomes may differ at various points throughout the lifespan (Hill et al, 2019). Indeed, past work taking this lifespan approach has found differential predictive validity using childhood and adult-based personality (Wright & Jackson, 2022b), and the current study shows that this matters at different points in adulthood as well. Overall, the different information gleaned by knowing someone's typical level of a trait and how they proceed to change in this trait is vital to fully understand their current and future development, and future research would greatly benefit from continuing to incorporate these two aspects of personality development when predicting consequential life outcomes.…”
Section: Effects Of Changes In Personality Traits Compared To Levelsmentioning
confidence: 53%
See 1 more Smart Citation
“…According to the differential pathways hypothesis, the pathways that explain why personality traits impact future outcomes may differ at various points throughout the lifespan (Hill et al, 2019). Indeed, past work taking this lifespan approach has found differential predictive validity using childhood and adult-based personality (Wright & Jackson, 2022b), and the current study shows that this matters at different points in adulthood as well. Overall, the different information gleaned by knowing someone's typical level of a trait and how they proceed to change in this trait is vital to fully understand their current and future development, and future research would greatly benefit from continuing to incorporate these two aspects of personality development when predicting consequential life outcomes.…”
Section: Effects Of Changes In Personality Traits Compared To Levelsmentioning
confidence: 53%
“…Conscientiousness, one of the traits most strongly related to various outcomes, predicts occupational performance and success (Anderson et al, 2001;Barrick et al, 2001), longevity (Jackson et al, 2015), engagement in health and risk behaviors (Bogg & Roberts, 2004;Friedman et al, 2014;Wright et al, 2022), and relationship quality (Solomon & Jackson, 2014). Neuroticism likewise has many strong associations: higher levels predict lower well-being (Smith & Spiro, 2002), psychopathology (Trull & Sher, 1994;Wright & Jackson, 2022b), interpersonal problems (Karney & Bradbury, 1997), and poorer relationship quality (Donnellan et al, 2005). Lastly, openness predicts political views (Saucier, 2000;Van Hiel et al, 2004), occupational interests (Barrick et al, 2003, Larson et al, 2002, and creativity (Peterson & Seligman, 2004).…”
Section: Why Personality Change Should Be Associated With Life Outcomesmentioning
confidence: 99%
“…Similarly, for selection effects that were negative in direction, seeing a mental health professional (2/2 datasets), receiving government financial assistance (3/3 datasets), and unemployment (4/4 datasets) were the life events with replicable effects. The life events with positive selection effects are all associated with "mature" personality trait profiles, whereas opposite associations occur for those that had negative selection effects (Beck & Jackson, 2022a;Soto, 2019;Wright & Jackson, 2022c). Importantly, the replication across datasets suggests the attracting traits associated with these events are consistent in different environments.…”
Section: Event-and Study-specific Associationsmentioning
confidence: 82%
“…This pattern of selection effects is consistent with previous personality development research. For instance, past work has found that individuals with higher levels of traits such as conscientiousness and agreeableness and lower levels of neuroticism are typically more likely to be employed, get married, and finish college, whereas the opposite is true of events such as divorce, unemployment, and mental health events (Beck & Jackson, 2022a;Ozer & Benet-Martínez, 2006;Soto, 2019;Wright & Jackson, 2022c). Higher levels of profile consistency are associated with these "mature" personality traits (i.e., high agreeableness and conscientiousness, low neuroticism; Donnellan et al, 2007;Wright & Jackson, 2022a).…”
Section: Life Events Have Many Selection Effects Fewer Socialization ...mentioning
confidence: 99%
“…Maternal emotional stability similarly predicted both lower infant reactivity and relevant context factors (e.g., increased depressive symptoms; lower social support and paternal income). In turn, these early temperament traits have been found to predict children's life outcomes 55 . Together, findings raise testable hypotheses that intergenerational outcomes of parental personality could operate at least in part via the perinatal social ecology into which children are born, through accumulation of parental health, interpersonal, and social capital, consistent with the concept of intergenerational niche construction 56 .…”
Section: Discussionmentioning
confidence: 99%